Pengembangan Prototipe Alat Peraga Styrofoam Sirkulasi Peredaran Darah Manusia pada Pembelajaran IPA SMP - Fatikhin, Achmad Choirul; Mahdiannur, Muhamad Arif; Putri, Fitriana Afianto; Subekti, Hasan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
One of the obstacles for students when studying the human circulatory system is the difficulty of students in distinguishing the large circulatory system and the small circulatory system. The purpose of developing the prototype of props is to make students better understand in real and detailed terms about the blood circulation process in the human body, so far, students have only used images as visual media, and students can be motivated and learning is not spared, so that student learning outcomes can improve. The purpose of making a circulatory system model of children's learning motivation is to provide a concrete picture of information and new ideas and unite the material that the teacher will convey to the knowledge that will be given to the child, so that the material presented by the teacher can be well received by students. Props are made using styrofoam material, which is designed in such an attractive way to be representative of human blood circulation. This research is part of design-research with small-scale class trials. A small-scale trial of a prop prototype involved seven junior high school students in Bojonegoro Regency, East Java. After being given an explanation and participants tried the prop prototype, they were given a questionnaire to measure students' interest and motivation for the prototype props that had been developed previously. The result obtained from this study is that students have new experiences by learning to use props. Participants were very interested and motivated in using prototypes of human circulatory circulation styrofoam props. The results of small-scale trials indicate that the props prototypes that have been developed are suitable for use in large-scale trials. Keywords: Teaching aids, blood circulation, science learning